2017
DOI: 10.1186/s12958-017-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rates of day 4 and day 5 embryos after culture in an integrated time-lapse incubator

Abstract: BackgroundThe aim of this study was to compare pregnancy rates in patients undergoing IVF/ICSI with embryo transfer after 4 and 5 days of culture in a closed incubation system with integrated time-lapse imaging.MethodsOut of n = 2207 in vitro fertilization (IVF)/ intracytoplasmic sperm injection (ICSI) cycles performed between January 2011 and April 2016 at a tertiary referral university hospital, a total of n = 599 IVF/ICSI cycles with prolonged embryo culture in an integrated time-lapse system (EmbryoScope© … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
(44 reference statements)
2
12
0
Order By: Relevance
“…Thereafter, full texts were screened seeking for ultimately relevant articles, as well as the reference lists of selected relevant publications were assessed for final inclusion. This thorough screening resulted in a total of 15 studies [5,6,8,13,[17][18][19][20][21][22][23][24][25][26][27] that are employed for the present meta-analysis. In Fig.…”
Section: Search Strategymentioning
confidence: 99%
See 4 more Smart Citations
“…Thereafter, full texts were screened seeking for ultimately relevant articles, as well as the reference lists of selected relevant publications were assessed for final inclusion. This thorough screening resulted in a total of 15 studies [5,6,8,13,[17][18][19][20][21][22][23][24][25][26][27] that are employed for the present meta-analysis. In Fig.…”
Section: Search Strategymentioning
confidence: 99%
“…Fifteen studies [5,6,8,13,[17][18][19][20][21][22][23][24][25][26][27] reported results on clinical pregnancy rates per ET cycle. Five different study designs (D4 vs. D3; D4 vs. D5; D4 vs. D2/3; D4 vs. D3/5; D4 vs. D2/3/5) comparing a total of four different days including 11,034 ET cycles were evaluated.…”
Section: Clinical Pregnancy Per Etmentioning
confidence: 99%
See 3 more Smart Citations